Building a Digitally Wise Generation: Gadget and Online Game Education at SD Negeri 03 Koto Bangun, West Sumatra - Setiawan, Daryanto; Candra Gunawan; Bahrul Ulum; Ifran Rivaldo (ASSUNNAH PRESS, 2026)
The rapid proliferation of digital technology has fundamentally altered the social landscape of children in Indonesia, including those in rural communities. Unregulated use of gadgets and online games among primary school pupils has been identified as a growing concern, contributing to the erosion of moral values, academic disengagement, and the weakening of family and social bonds—a condition acutely observed at SD Negeri 03 Koto Bangun, Nagari Koto Bangun, Kapur IX Sub-district, Lima Puluh Kota Regency, West Sumatra. This article aims to describe the implementation of a digital literacy education programme conducted as part of the Thematic Community Service Programme (Kuliah Kerja Nyata Tematik, KKNT) by students of STAI As-Sunnah Deli Serdang, while examining the effectiveness of the service learning approach as a community-based educational intervention. The community service partners comprised 191 participants, consisting of 127 pupils from Years 1 to 6, 11 teachers and educational staff, and 53 parents and guardians of SD Negeri 03 Koto Bangun. The programme was implemented through the five-stage service learning methodology: investigation, planning, action, reflection, and demonstration, conducted from 3 to 17 March 2025. The findings demonstrate that the programme succeeded in raising collective awareness among pupils, teachers, and parents regarding the adverse effects of unregulated gadget and online game use, and in fostering positive digital habits within the school community. Service learning proved to be an effective and replicable model for community-based digital literacy education, yielding a double-impact upon both community development and the professional formation of students as socially committed Muslim intellectuals.